Life dances on Robert Frank in dialogue - Frank, Robert 1924-2019; Gallun, Lucy; Booher, Kaitlin; Greenough, Sarah 1951-; Hall, Emily ca. 20. Jh (The Museum of Modern Art, 2024)
"For the Swiss-born photographer Robert Frank, the year 1958 marked, as he later noted, "the beginning of something new." Having completed the selection of images for his photobook The Americans, Frank embarked on a path of creative exploration that lasted six decades, until his death in 2019. Across mediums, in photography, film, video, and books, his work reckoned with the death of loved ones and the passage of time. In collaborations with writers, musicians, publishers, and other artists, he also reflected on his role in a community of artists and neighbors, both in New York City and Cape Breton, Nova Scotia, where he and his wife, the artist June Leaf, moved in 1970. Life Dances On: Robert Frank in Dialogue is the first solo exhibition of Frank's work at The Museum of Modern Art, presented on the occasion of Frank's centennial".
Keywords: Frank, Robert -- 1924-2019; Ausstellungskatalog -- The Museum of Modern Art -- 15.09.2024-11.01.2025 -- New York, NY